Clinical outcomes of arthroscopic triangular anchor-stellate suture technique for massive L/U-shaped rotator cuff tears - Weipeng Zheng; Weipeng Zheng; Zhengfeng Ye; Yuke Song; Yuke Song; Zhijun Liu; Zhijun Liu; Zhihao Liao; Zhihao Liao; Sheng Chen; Sheng Chen; Suming Zheng; et al. (Frontiers in Surgery)
BackgroundMassive rotator cuff tears are a major cause of shoulder pain and limited function. While arthroscopic repair is common, treating complex L- or U-shaped tears, which involve tendon retraction and uneven tension, remains difficult. Specialized surgical methods are needed to restore normal anatomy and improve function. New arthroscopic techniques, like combined anchor placement and advanced suture methods, show potential for better tendon healing. But more research is needed to confirm their effectiveness specifically for L- or U-shaped tears.PurposeTo investigate the efficacy of the arthroscopic Triangular Anchor-Stellate Suture technique in the treatment of Massive L/U-shaped Rotator Cuff Tears.MethodsBetween January 2022 and December 2023, 22 patients (8 males, 14 females) with massive rotator cuff tears (L or U shape) underwent arthroscopic repair using the Triangular Anchor-Stellate Suture technique. Disease duration ranged from 2 weeks to 12 months (median, 3 months). According to the DeOrio and Cofield classification, all tears were categorized as “L” or “U” type. Clinical outcomes were assessed by recording postoperative complications and comparing pre- and postoperative pain (VAS), shoulder range of motion (ROM), Constant-Murley score, ASES score, and modified SF-12 quality of life score. Pre- and postoperative imaging was performed using CT or MRI.ResultsPatients' wounds healed in stage I without infection. They were followed up for an average of 17.59 ± 6.07 months (12–18 months). VAS scores decreased from 7.68 ± 1.04 preoperatively to 1.23 ± 1.45 postoperatively (P < 0.05). Shoulder range of motion improved significantly (P < 0.05): flexion increased from 71.82 ± 12.11° to 152.05 ± 23.23°, abduction from 68.64 ± 11.25° to 145.00 ± 22.41°, external rotation from 41.82 ± 13.32° to 57.27 ± 12.02°, and internal rotation from 37.95 ± 7.51° to 55.00 ± 7.56°. Shoulder function scores also improved significantly (P < 0.05): Constant-Murley score rose from 38.59 ± 8.43 to 86.27 ± 9.03, and ASES score from 38.32 ± 7.52 to 85.95 ± 8.13. Quality of life scores, as measured by the SF-12, improved significantly (P < 0.05): PCS score increased from 26.27 ± 4.71 to 45.18 ± 5.84, and MCS score from 24.72 ± 5.18 to 41.18 ± 4.52. Postoperative CT scans showed that all patients' humeral heads had moved downwards and returned to their normal rotation center. The last follow-up MRI examination revealed no further tearing of the rotator cuff.ConclusionThe arthroscopic Triangular Anchor-Stellate Suture technique demonstrates significant clinical efficacy in managing massive L/U-shaped rotator cuff tears, providing effective pain relief, enhanced shoulder mobility, functional restoration, and improved quality of life outcomes.